Tecnologias digitais e formação docente: vivências de uma licenciatura em matemática - Freitas, Wesley Emannuel Ribeiro de (2023)
In an increasingly digitally connected world, Digital Technologies (DT) have transformed the ways of producing and disseminating knowledge. Likewise, it can be said that new tensions emerged in studies on the use of DT in education during the COVID-19 pandemic, a historical moment in which it was possible to witness, in the face of the demands of social isolation, the transposition of face-to-face teaching to the so-called Emergency Remote Education (ERE). Thus, faced with then anomalous contexts, educators realized the need to rethink their educational practices, adapting to the new contingencies given the pandemic situation, providing the construction of new contexts and pretexts on the pedagogical practice of teachers at different levels of education, crossed by limits and possibilities. Such findings also imply considering the experiences of undergraduate students at face-to-face teaching universities both in the context of their training and in the first contacts with classrooms through the mandatory internship, as well as teaching initiation scholarships or pedagogical residency. In this context, the Mathematics Degree course at the Federal Technological University of Paraná (UTFPR), Pato Branco campus, is a relevant space for studying the diversity in the forms of use and appropriation of DT in Mathematics Education, and can generate relevant data for analysis in order to contribute to Mathematics Education, with the educational praxis of Mathematics in the municipality of Pato Branco and in the state of Paraná. Under this pretext, structuring this research with a qualitative and descriptive character, it aims to analyze the forms of use and appropriation of DT as mediations within the scope of teacher training of the Mathematics Degree Course, in the context of the Federal Technological University of Paraná (UTFPR) campus Pato Branco. Interviews and focus groups were conducted with teachers and students of this respective course, using a script pre-established by the author. For data analysis, the researcher used the techniques of Content Analysis, establishing categories that related the set of knowledge of the Specialized Knowledge of the Mathematics Teacher (MTSK) and the DT. With this research, it was possible to observe in the manifestations of teachers and students of a mathematics teacher training course the transformations that occurred in the production and dissemination of knowledge, as well as the new relationships established with the use of DT to mediate educational práxis.